Pathology specific secondary aortic interventions after thoracic endovascular aortic repair - Scali, Salvatore T. (2014)
OBJECTIVE: Despite improved short-term outcomes, concerns remain regarding durability of thoracic endovascular aortic repair(TEVAR). The purpose of this analysis was to evaluate the pathology-specific incidence of secondary aortic interventions(SAI) after TEVAR and their impact on survival. METHODS: Retrospective review was performed of all TEVAR procedures and SAI at one institution from 2004-2011. Kaplan-Meier analysis was used to estimate survival. RESULTS: Of 585 patients, 72(12%) required SAI at a median of 5.6 months(interquartile range(IQR):1.4-14.2) with 22(3.7%) requiring multiple SAI. SAI incidence differed significantly by pathology(P=.002): acute dissection(21.3%), post-surgical(20.0%), chronic dissection(16.7%), degenerative aneurysm(10.8%), traumatic transection(8.1%), penetrating ulcer(1.5%), and other etiologies(14.8%). Most common indications after dissection were persistent false lumen flow and proximal/distal extension of disease. For degenerative aneurysms, SAI was performed primarily to treat type I/III endoleaks. SAI patients had a greater mean number of comorbidities(P<.0005), stents placed(P=.0002), and postoperative complications after the index TEVAR(P<.0005) compared to those without SAI. Freedom from SAI at 1 and 5 years(95% CI) was estimated to be 86%(82-90%) and 68%(57-76%), respectively. There were no differences in survival(95% CI) between patients requiring SAI and those who did not: SAI 1-year: 88%(77-93%), 5-year: 51%(37-63%) and no SAI 1-year: 82%(79-85%), 5-year: 67%(62-71%)(Log-rank P=0.2). CONCLUSION: SAI after TEVAR is not uncommon, particularly in patients with dissection, but does not affect long-term survival. Aortic pathology is the most important variable impacting survival and dictated need, timing and mode of SAI. The varying incidence of SAI by indication underscores the need for diligent surveillance protocols that should be pathology-specific.